Crecimiento Económico con Pobreza y Desigualdad en Colombia (2009)
The present article, shows that problems concerning poverty and inequity must be faced and treated with policies that, while still promoting a country’s economic growth, should involve actions seeking to reduce the inequalities existing between members of a society. In such a case, the state should implement support strategies for the poorest part of the population with the goal of raising their productivity and thus augmenting their possibilities of an active enrollment in the labor market along with an income that can help to fully satisfy their needs. In this perspective, the matter of education claims a leading role, taking into account subjects ranging from theoretical advances directly akin to the topic of economic growth to the empirical evidence available on the issue. Such demonstration is accomplished by starting from a revision of literature regarding economic growth and making a critical analysis of the Colombian economy’s diagnosis, emphasizing on the variables that relate directly to the problem being considered.